Extra-Oral Sinuses Of Dental Origin - Din, Qiam ud; Sattar, Fazal (Journal of Postgraduate Medical Institute, 2011)
This article concerns four patients with cuteneous sinus tracts of dental origin who were referred to Oral and Maxillofacial Surgical Unit of Oral and Dental Hospital, Peshawar. These cases demonstrate that once the correct diagnosis has been made, treatment by appropriate surgical procedures, direct towards the source of infection leads to prompt resolution of the sinus tract. This is an uncommon disease but one for which a high degree of alertness must be maintained when one sees a nodulocystic or ulcerative lesion of the face.